Drought stress reduces grain yield by altering floral meristem development and sink size dry-seeded rice cultivation - Quinones, Cherryl; Mattes, Nico; Faronilo, James; Sudhir-Yadav; Jagadish, Krishna S.V. (Wiley, 2017)
Water and labor shortages are currently driving the shift from continuously flooded, puddled transplanted rice (Oryza sativa L.) (PTR-cf) to alternative crop establishment practices, such as dry-seeded rice (DSR). To improve water productivity by using DSR, fields are often kept under aerobic conditions. This shift could induce sensitivity to critical developmental processes during the early reproductive stages such as floral meristem (panicle) initiation and growth, when this coincides with water-limited conditions. To study the physiological impact of different establishment methods with different water available conditions, rice cultivar NSICRc 222 was evaluated, under PTR-cf, dry-seeded rice (DSR) with daily irrigation (DSR-d) and DSR with cyclic irrigation whenever soil water tension reached 10 kPa (DSR-10) and 40 kPa (DSR-40). Young developing inflorescences showed a morphological shift towards a slender shape under DSR-10 and a further increase in slenderness under DSR-40. We document a significant negative impact on developing inflorescence differentiation, a reduction in panicle neck diameter, and lower panicle nonstructural carbohydrate (NSC) content and grain length with a shift from PTR-cf to DSR-d. Key physiological traits such as retaining a globular-shaped floral meristem as a marker for optimal spikelet number and increased panicle sink size and panicle neck diameter, and NSC content for minimizing yield penalty are recommended when developing rice varieties for DSR, particularly under water-limited DSR conditions